FACADE SURVEYING USING TRADITIONAL ANGULARLINEAR MEASUREMENTS AND 2D SOFTWARE: FACADE SURVEYING USING TRADITIONAL ANGULARLINEAR MEASUREMENTS AND 2D SOFTWARE - Ivanov, Ivan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
To solve complex urban planning and architectural-artistic tasks related to the determination of the spatial location of the existing external elements of the building, in practice it is often necessary to carry out geodetic surveying of building facades. Photographing facades is used in reconstructions of buildings or restorations of cultural monuments, preservation of cultural heritage, photographing archaeological sites, carrying out various types of research activities and analyses, designing suspended facades, cladding and joinery, preparing a working layout plan etc.